Origins and futures : time inflected and reflected - Steineck, Raji C.; Clausius, Claudia (Study of time, 2013)
Origins and Futures: Time Inflected and Reflected offers an interdisciplinary approach to two fundamental often opposing concepts of time. The volume features both research on specific texts and authors as well as conceptual disciplinary reflections in the spirit of an integrated study of time.